Humor, empathy, and community in twentieth-century American poetry - Trousdale, Rachel (Oxford University Press, 2021)
For poets slightly outside of the literary or social mainstream, humour encourages mutual understanding and empathic insight among artist, audience and subject. As a result, laughter helps poets reframe and reject literary, political and discursive hierarchies - whether to overturn those hierarchies, or to place themselves at the top. 'Humor, Empathy, and Community in Twentieth-Century American Poetry' explores how American poets of the last hundred years have used laughter to create communities of readers and writers.
10.1093/oso/9780192895714.001.0001
Keywords: American poetry; Humor in literature; Laughter in literature; Empathy in literature; Communities in literature